2018
DOI: 10.15419/bmrat.v5i4.429
|View full text |Cite|
|
Sign up to set email alerts
|

Insertion / Deletion Polymorphism of Angiotensin Converting Enzyme Gene Does Not Contribute to Chronic Kidney Disease in Palestine

Abstract: Creative Commons Attribution License http://creativecommons.org/licenses/ by/4.0/, which permits unrestricted use, provided the original author and source are credited.Background: Chronic Kidney Disease (CKD) is progressive kidney damage in which the glomerular filtration rate (GFR) decreases by 15% of that performed by normal kidneys, with the result that the kidneys are no longer to function effectively and this condition is treated with either kidney transplantation or dialysis. Hemodialysis (HD) is a proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…As we showed in our previous study 22 , according to the initial results of the study no association between ACE genotype and nephropathy in the Gaza Strip can be approved, and this result again obtained with a different population while in a meta-analysis study by Schena et al (2001), who found that the D/D genotype could be associated with the development of nephropathy (1.96 of risk) 35 .…”
Section: The Relationship Between Ace Genotype and Nephropathymentioning
confidence: 59%
“…As we showed in our previous study 22 , according to the initial results of the study no association between ACE genotype and nephropathy in the Gaza Strip can be approved, and this result again obtained with a different population while in a meta-analysis study by Schena et al (2001), who found that the D/D genotype could be associated with the development of nephropathy (1.96 of risk) 35 .…”
Section: The Relationship Between Ace Genotype and Nephropathymentioning
confidence: 59%